Comparativo entre as tecnologias Frame Relay e MPLS VPN em camada 3 - Zanon, André Giacomelli (2015)
With the advancement of computer networks in advanced applications, the need for a technology to provide speed, scalability, quality of service management (QoS) and traffic engineering for a better cost / benefit compared to network technologies core as Frame Relay. The MPLS (Multi-protocol Label Switching) is able to ensure that each data packet to be delivered to its destination with its due priority, taking advantage of the maximum network resources. This paper aims to address the concept of MPLS, its advantages and disadvantages, a brief comparison with other technologies such as Frame Relay and finally demonstrate the practical application using the simulator GNS3 networks focusing on MPLS VPN (Virtual Private Networks).